The effect of gelatin hydrolysate from pygostyle of broiler produced by enzymatic hydrolysis process of Aspergillus niger to prophylaxis - YASMI PURNAMASARI KUNTANA; ROOSTITA BALIA; SAYUTI MURAD; YULI ASTUTI HIDAYAT; RUHYAT PARTASASMITA (Nusantara Bioscience, 2017)
Kuntana YP, Balia R, Murad S, Hidayat YA, Partasasmita R. 2017. The effect of gelatin hydrolysate from pygostyle of broiler produced by enzymatic hydrolysis process of Aspergillus niger to prophylaxis of osteoporosis white rat. Nusantara Bioscience 9: 361- 366. The pygostyle of the broiler is a cartilage tissue containing collagen, a mucoprotein being a plasma expander. The hydrolysis process of collagen by enzyme can produce gelatin hydrolysate differently compared to that from commercial gelatin because it has an amino acid composition with low average molecular weight. It becomes an advantage because it can be directly absorbed by the digestive tract. In addition, the enzymatic process can be done in short time with the low cost and also environment-friendly approach. This process can be assisted by Aspergillus niger, i.e., safe microorganisms (GRASS). A. niger has a protease enzyme that can digest collagen into gelatin hydrolysate. The enzyme is extracellularly removed so that its utilization does not require high input value expenditure. Gelatin hydrolysate can reduce the disease of osteoporosis. The objective of this study was to know the effect of gelatin hydrolysate produced from chicken bones in the favor of A. niger for increasing the benefit products. The specific targets are to find the amount of gelatin hydrolysate, precisely eliminated osteoporosis of rat (Rattus norvegicus). The experimental research was conducted in the laboratory with using complete randomized design followed by the descriptive analysis with 5 treatment and 5 replication. CCl4 dose 0,14 mL/g BW (P1 as a negative control), Potatoes dextrose Broth (PDB) dose 0,5 mL/g BW (P2 positive control), gelatin hydrolysate dose 0.25; 0.5; 0.75 mL/g BW (P3-P5). The observed parameters were including body weight and histological observation of musculoskeletal tissue in terms of measurement of fiber muscle, cartilage and collagen diameter. The test animal used was male white rat (R. norvegicus) Wistar strain aged 2-3 months with body weight 185-200 g. Data were analyzed using ANOVA and Duncan test. The results show that gelatin hydrolyzate as an environmentally friendly product serves as a prevention of immune diseases and degenerative diseases such as osteoporosis.